2009
DOI: 10.3201/eid1512.090390
|View full text |Cite
|
Sign up to set email alerts
|

Recombination in Vaccine and Circulating Strains of Porcine Reproductive and Respiratory Syndrome Viruses

Abstract: Em2007, a porcine reproductive and respiratory syndrome virus (PRRSV) variant with a unique 68 aa deletion in Nsp2, was recently isolated in China. Phylogenetic and molecular evolutionary analyses indicated that Em2007 is a natural recombinant between a vaccine strain of PRRSV and circulating virus. We also tested its pathogenicity in piglets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
92
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(95 citation statements)
references
References 12 publications
2
92
0
1
Order By: Relevance
“…Thus, its role in PRRS may be important due to the appearance of recombinants associated with outbreaks (Shi et al, 2013a) or identified circulating in significant numbers over wide geographical areas originating from common ancestors (Shi et al, 2013b) when in the past only sporadic instances were detected (Li et al, 2009a, b;Yoshii et al, 2008).…”
Section: Recombinationmentioning
confidence: 99%
“…Thus, its role in PRRS may be important due to the appearance of recombinants associated with outbreaks (Shi et al, 2013a) or identified circulating in significant numbers over wide geographical areas originating from common ancestors (Shi et al, 2013b) when in the past only sporadic instances were detected (Li et al, 2009a, b;Yoshii et al, 2008).…”
Section: Recombinationmentioning
confidence: 99%
“…In the The brains were analyzed for virus by RT-PCR as previously described. 8 Four sick pigs were positive for PRRSV by RT-PCR and were negative in the healthy inoculated pig and control group (data not shown; Fig. 2).…”
mentioning
confidence: 99%
“…This disease affected over 2,000,000 pigs and caused 400,000 fatal cases in more than 10 provinces. [6][7][8]13 The pigs infected by HP-PRRSV had the following atypical PRRS symptoms: neurological symptoms (e.g., shivering, lameness, and opisthotonus), high fever (40-42°C), and an erythematous blanching rash.…”
mentioning
confidence: 99%
“…The phylogenetic tree demonstrated that 3 recent isolates from Thailand (UD1210US/61-F03, UD1210US/61-G03, and UD1210US/61-E03) were more genetically related to CH-1R (an attenuated vaccine strain used in PRC) than HP-PRRSV (Figure 2). CH-1R is a classical PRRSV from PRC that does not possess the 2 discontinuous 30-aa deletions in Nsp2 (15). Furthermore, CH-1R is an attenuated PRRSV vaccine strain in PRC, and there is evidence that it has been illegally smuggled into Thailand.…”
Section: The Studymentioning
confidence: 99%